Development of canned "Escabeche" from Alumahan (Rastrelliger chrysozonus) - Wan, Aurea F.; Gatchalian, Miflora M. (1974.)
Canned "escabeche" was developed from alumahan utilizing varying formations, pre-treatment and processing time. The product was analyzed both objectively and subjectively. heat penetration studies were also conducted to supplement the study o effectivity of shorter processing time (60 and 75 minutes). Results showed that the best product was one which steamed for 8 minutes and processed for 60 minutes at 240°F. The standardized canned "escabache" was described by the taste panel as having a yellowish to brownish yellow sauce, golden brown flesh, tender flesh and bones, moderately sweet-sour to characteristic sweet-sour odor and flavor. The rating for general acceptability was "like moderately" to "like very much".
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Canned fish